ANALISIS PERILAKU KEUANGAN ANTARA RUMAH TANGGA MISKIN DAN NON MISKIN DI PROVINSI GORONTALO - Risti Pomalingo; Sri Endang Saleh; Boby Rantow Payu (Jurnal Maneksi (Management Ekonomi Dan Akuntansi), 2026)
Introduction: This study aims to analyze differences in financial behavior between poor and non-poor households in Gorontalo Province and to identify the socio-demographic, economic, and financial access factors that influence these differences. Poverty in the region remains a significant issue and is closely related not only to income levels but also to financial behavior and access to economic resources.Methods: The study employed a descriptive, quantitative approach, using secondary data from the National Socio-Economic Survey (Susenas) and official publications from the Central Statistics Agency (BPS). The analysis focused on spending patterns, savings and investment behavior, debt management, financial planning, and household socio-demographic characteristics.Results: In September 2024, the poverty rate in Gorontalo Province was 13.87 percent, or approximately 107,030 people, with an average household poverty line of IDR 2,837,704 per month. Poor households had an average family size of 5.14 persons, higher than non-poor households at 4.03 persons. The education level of poor household heads was generally lower, and their income tended to be unstable, leading to a larger proportion of expenditure allocated to basic needs. In contrast, non-poor households demonstrated greater capacity to allocate income toward savings, investments, and non-essential consumption, as well as better access to formal financial services.Conclusion and Suggestion: This study confirms that poverty in Gorontalo Province is influenced not only by income disparities but also by financial behavior, education level, financial literacy, and access to financial institutions. These findings provide an evidence-based foundation for local governments and stakeholders to design more targeted and sustainable poverty alleviation policies, strengthen financial literacy programs, and promote inclusive household economic empowerment initiatives. Keywords: Poor Households, Poverty, Urban, Rural